Research on Common Cognitive Biases and Mutual Influence in Corporate Decision Making - Yuwen Xinuo (SHS Web of Conferences)
This paper investigates the critical effect of cognitive biases on corporate decision-making, with a center on how these predispositions can lead to suboptimal outcomes, missed opportunities, or indeed catastrophic failures. Drawing on the previous work, the investigation distinguishes ten common inclinations that as often as possible influence commerce choices. The essential objective is to explore whether recognizing a key cognitive predisposition might rearrange the acknowledgment and administration of other related predispositions. The considered hypothesis states that that a few inclinations may have a foundational part, possibly activating or opening others. By focusing on this “core bias”, decision-makers might moderate the broader impact of numerous predispositions, making strides in choice quality and organizational performance. To prove those proposals above, this paper recites several relevant experiments. By comparing and cogitating their conclusion with the author’s own opinions, the author discoveries point to supplying senior supervisors with improved apparatuses for rational decision-making, eventually cultivating a more objective corporate culture and driving supported victory within the competitive global market.